Antioxidant White Grape Seed Phenolics: Pressurized Liquid Extracts from Different Varieties - Carmen Garcia-Jares; Alberto Vazquez; Juan P. Lamas; Marta Pajaro; Marta Alvarez-Casas; Marta Lores (MDPI AG, 2015)
Grape seeds represent a high percentage (20% to 26%) of the grape marc obtained as a byproduct from white winemaking and keep a vast proportion of grape polyphenols. In this study, seeds obtained from 11 monovarietal white grape marcs cultivated in Northwestern Spain have been analyzed in order to characterize their polyphenolic content and antioxidant activity. Seeds of native (Albariño, Caiño, Godello, Loureiro, Torrontés, and Treixadura) and non-native (Chardonnay, Gewurtzträminer, Pinot blanc, Pinot gris, and Riesling) grape varieties have been considered. Low weight phenolics have been extracted by means of pressurized liquid extraction (PLE) and further analyzed by LC-MS/MS. The results showed that PLE extracts, whatever the grape variety of origin, contained large amounts of polyphenols and high antioxidant activity. Differences in the varietal polyphenolic profiles were found, so a selective exploitation of seeds might be possible.